The Creation Process of Dewanggono Dance Works in the Tradition of Arak Tumpeng Ponco Tuk - Purwaningsih, Dewi; Kusumo Wibowo , Anggono; Samsuri (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2026)
This study examines the Siraman Kepemimpinan procession and Buddhist teachings, focusing on the concepts of Prajnaparamita and Panca Skandha as the primary inspiration for the Dewanggono dance. The objective is to create a new choreography that embodies the values of wisdom and inner purity, grounded in the understanding that the human self consists of five impermanent aggregates. Five dancers participated in the exploration of the inner journey from emptiness to perfection across four acts, each expressing different mental states through movement and body language. The research method employed was Practice Led Research, which integrates field research with dance creation theory, encompassing the stages of design, development, composition, and performance. Data analysis involved evaluations and guidance from a supervising lecturer, with a focus on enhancing the message and harmony between the movement and the accompanying Javanese gamelan music. The findings indicate that this dance not only emphasizes aesthetic and technical elements but also conveys a profound spiritual message regarding purity and wisdom in life. In conclusion, Dewanggana has successfully emerged as a dance work that balances visual beauty with the philosophical richness of Buddhist teachings and the local traditions of Pakel village.